A SiO x -M@C-G composite material and preparation method thereof, and lithium ion battery

CN116936752BActive Publication Date: 2026-10-27NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210318893.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-29
Publication Date
2026-10-27
Estimated Expiration
2042-03-29

AI Technical Summary

Technical Problem

[0003]目前在这方面的研究多以金属和金属盐与微米SiO复合,但制备工艺复杂,需要先制备SiO,在利用金属和金属盐与微米SiO,并且只是在微米SiO表面进行反应包覆,没有完全掺杂到微米颗粒中去,而且表面包覆效果较差,表面包覆层厚度难以控制,厚度增大影响锂离子的传输,进而材料的电化学电性能

Benefits of technology

[0054]本发明提供的SiOx-M@C-G复合材料的制备工艺简单,可控性好,条件温和,更加适于工业化推广和应用。本发明的制备工艺中,金属在低温区不会产生蒸汽,反应安全性大大提高,有效的解决了现有的同类型硅基复合负极材料的制备方法,采用SiO和金属同时蒸发成气体,气体混合后在低温区混合凝结的方式,存在耗能高,金属蒸汽制备存在安全风险,并且SiO和金属的凝结温度不同,制备的物料组分无法控制,杂质成分多,管道中也容易积累冷凝的物料等问题;而且所用的设备双炉膛,双温区控制,需要设计专用设备,费时费力等缺陷。采用本发明提供的硅碳复合材料作为锂离子电池复合材料,无定型碳-石墨烯复合结构和M金属掺杂能提高氧化硅碳颗粒的电导率,进而增加电池倍率性能;M金属掺杂能提高氧化硅碳的首次率,并能有效的抑制SiO在充放电过程中的体积膨胀;无定型碳-石墨烯复合造粒结构能稳定,更能够有效的抑制氧化硅碳膨胀。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003570839100000011
    Figure HDA0003570839100000011
  • Figure HDA0003570839100000012
    Figure HDA0003570839100000012
  • Figure HDA0003570839100000021
    Figure HDA0003570839100000021
Patent Text Reader

Abstract

This invention provides a SiO x -M@C-G composite material and its preparation method. This invention provides SiO₂ with a specific structure and composition. x In the -M@C-G composite material, the graphene composite three-dimensional structure can provide SiO2 x The volume expansion of M-particles provides space, while the in-situ growth of amorphous carbon improves the electrical conductivity and structural stability of the composite material, reduces the volume expansion of the material during charging and discharging, and the graphene coating reduces the SiO2 content. x The increased contact area between -M and the electrolyte improves the stability of the SEI film in the composite material, enhancing its cycle efficiency and stability. The increased conductivity also contributes to the high rate performance of the composite material. The SiO2 provided by this invention... x The preparation process of the M@C-G composite material is simple, controllable, and mild. The metal does not generate vapor in the low-temperature region, which greatly improves the safety of the reaction and makes it more suitable for industrial promotion and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of lithium battery anode materials, and relates to a SiO2-based anode material. x -M@CG composite materials and their preparation methods, lithium-ion batteries. Background Technology

[0002] Lithium-ion batteries possess advantages such as high operating voltage, high specific energy, long cycle life, light weight, low self-discharge, no memory effect, and high performance-price ratio, making them the primary choice for rechargeable power sources in high-power electric vehicles, satellites, aerospace, and other fields. Especially in practical applications, lithium-ion batteries have become an ideal energy source for various portable electronic devices, such as laptops and mobile phones. In recent years, the rapid development of new electric devices such as electric vehicles, particularly the fact that the range of new energy vehicles depends on the energy density of batteries, has led to increasingly higher consumer demands for vehicle range. High energy density has become the future development direction for power batteries. The energy density of lithium-ion batteries mainly depends on the lithium storage capacity and voltage of the positive and negative electrode materials. There are two directions for solving this problem: first, developing high-capacity, high-potential positive electrode materials; second, developing high-capacity, low-potential negative electrode materials. Therefore, the negative electrode material also determines the performance of lithium-ion batteries and is a key factor affecting their performance. However, traditional commercial lithium-ion battery negative electrode materials, such as graphite, have a relatively low theoretical specific capacity (372 mAh g / g). -1 The low rate performance and low discharge voltage of silicon-based anodes can lead to lithium deposition and a series of safety issues. With the potential of traditional graphite anodes in terms of energy density already fully explored, silicon-based anodes have become one of the best solutions for improving energy density in power batteries. Silicon-based materials use an alloying reaction process to store energy and have an ultra-high theoretical specific capacity of 4200 mAh / g. However, silicon anode materials experience volume expansion of up to 300% during lithium insertion / extraction, and their poor conductivity causes silicon particles to break and pulverize, preventing the formation of a stable SEI film. After several cycles, capacity decays severely, making them unsuitable for standalone application in lithium-ion batteries. Therefore, they need to be combined with carbon materials that have excellent conductivity and can accommodate silicon volume changes to significantly improve energy density and cycle stability. Currently, the main approaches to improve the cycle performance of silicon-based anode materials are silicon nano-sized (<150 nm), silicon alloyed with other metals, and silicon combined with inert or active matrices. Furthermore, the formation of nano-silicon-carbon composite materials with carbon mechanisms can alleviate excessive volume expansion, maintain the structural stability of nano-silicon, and improve the material's cycle and rate performance.

[0003] Current research in this area mainly focuses on composites of metals and metal salts with micron-sized SiO. However, the preparation process is complex, requiring the prior preparation of SiO before reacting with micron-sized SiO using metals and metal salts. Furthermore, the reaction coating only occurs on the surface of the micron-sized SiO, without complete doping into the micron-sized particles. The surface coating effect is also poor, and the thickness of the coating layer is difficult to control. Increased thickness affects lithium-ion transport, thus impacting the electrochemical and electrical properties of the material. For example, most current techniques for preparing similar materials only involve surface coating, using a mixture of metals or metal salts or ball milling to react with SiO to form metal silicates. This only creates a surface coating layer, making it difficult to control the thickness. Moreover, such surface coatings are almost non-conductive, resulting in even lower conductivity of the SiO material, and the coating layer is prone to detachment. The composite material also suffers from significant polarization during charge and discharge, leading to poor rate performance, among other problems. As disclosed in patent application 202010542046.1, aluminosilicate is coated onto the surface of SiO by ball milling. However, this method has problems such as poor coating uniformity, aluminosilicate easily hindering lithium ion transport, insignificant improvement in initial efficiency and rate performance, and greater difficulty in industrialization.

[0004] Therefore, how to obtain a more suitable silicon-carbon composite anode material that can solve the above problems, improve the conductivity of SiO particles while reducing the oxygen content of SiO to improve the electrochemical and electrical performance of the material, has become one of the focuses of attention for many leading researchers in this field. Summary of the Invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a SiO x -M@CG composite material and its preparation method, and lithium-ion battery. The silicon-carbon composite material provided by this invention effectively suppresses the volume expansion of SiO during charge and discharge, and has better cycle efficiency and cycle stability. It also improves the stability of the SEI film of the composite material and enhances its conductivity. Moreover, the preparation process is simple, has good controllability, and is suitable for industrial promotion and application.

[0006] This invention provides a SiO x -M@CG composite material, including: multiple SiO x -M@C particles;

[0007] Composite in single and / or multiple SiO x Graphene sheets on M@C particles;

[0008] Where 0.1 ≤ x ≤ 0.9; M is a metal and / or a metal salt;

[0009] The plurality of SiO x -M@C particles, and / or, SiO x-Amorphous carbon is present between the M@C particles and the graphene sheets;

[0010] The SiO x -M@C particles include SiO x -M particles and coatings on SiO x -M Amorphous carbon layer on the surface of particles.

[0011] Preferably, the composite material is a three-dimensional spherical and / or ellipsoidal composite material with graphene microsheets encapsulated in the inner and outer layers.

[0012] The composite material is a porous material;

[0013] The specific surface area of ​​the composite material is 2~6 m². 2 / g;

[0014] The pore size of the composite material is 10~2μm;

[0015] The particle size of the composite material is 8~50μm.

[0016] Preferably, the composite material contains SiO x The mass ratio of M, C to graphene is 100:(1~6):(1~15):(5~50);

[0017] The SiO x The particle size is 100 nm to 10 μm;

[0018] The graphene sheet diameter is 200 nm to 20 μm;

[0019] The number of graphene sheets includes 1 to 30 layers;

[0020] The thickness of the amorphous carbon layer is 1~200 nm.

[0021] Preferably, the SiO x -M@C particles have a core-shell structure;

[0022] The plurality of SiO x -M@C particles are encased in a cage-like structure within graphene sheets;

[0023] The SiO x -M@C particles specifically consist of multiple SiO2 particles. x -M particles form secondary particles, and an amorphous carbon layer coats the surface of the secondary particles;

[0024] The metal includes one or more of the elements aluminum, magnesium, tin, silver, germanium, sodium, and nickel.

[0025] Preferably, the secondary particles are particles with pores on the surface and / or inside;

[0026] The particle size of the secondary particles is 1μm~20μm;

[0027] The surface and / or internal pores also contain M particles;

[0028] The SiO x -M includes SiO x Complexes formed with metals, SiO x Complexes formed with metal salts and SiO x One or more of the complexes formed with metal silicates;

[0029] The SiO x Complexes formed with metals, SiO x Complexes formed with metal salts and SiO x The complexes formed with metal silicates have one or more of the following linkages: coating, doping, intercalation, and chemical bonding.

[0030] Preferably, the M is doped in SiO x The interior and surface of the particles;

[0031] The plurality of SiO x -M@C particles, and / or, SiO x -M@C particles are connected to graphene sheets through amorphous carbon;

[0032] The amorphous carbon has a framework structure;

[0033] The composite material is a negative electrode active material;

[0034] In the composite material, silicon-based active materials account for more than 60% of the total mass of the composite material.

[0035] This invention provides a SiO x The preparation method of -M@CG composite material includes the following steps:

[0036] 1) After mixing SiO2 and Si, a powder mixture is obtained. This powder mixture is then subjected to vacuum high-temperature treatment to form SiO2. x Gas, then SiO x Gas is introduced into a vacuum low-temperature zone containing M metal powder and / or M metal salt, SiO x The gas is passed through a device containing M metal powder and / or M metal salt to obtain SiO. x -M precursor;

[0037] 2) Under protective gas conditions, the SiO2 obtained in the above steps is... x - After heating the M precursor, a carbon-containing reaction gas is introduced, and after chemical vapor deposition, SiO is obtained. x -M@C materials;

[0038] 3) The SiO obtained in the above steps x -M@C materials, dispersants, additives, water-soluble carbon sources, and graphene aqueous dispersions are mixed and then granulated to obtain SiO2. x -M@CG precursor, then sintered under a protective atmosphere to obtain SiO x -M@CG composite material.

[0039] Preferably, the vacuum pressure of the high-temperature vacuum is 0.01~100 Pa;

[0040] The temperature of the vacuum high temperature is 1300~1500℃;

[0041] The vacuum high-temperature treatment time is 5~10 hours;

[0042] The temperature of the vacuum cryogenic temperature is 300~500℃;

[0043] The SiO x The D50 particle size of the -M precursor is 100 nm to 10 μm.

[0044] Preferably, the dispersant comprises one or more of polyethylene glycol, polyacryl alcohol, Tween-60, Tween-80, sodium dodecyl sulfonate, and sodium dodecyl sulfate;

[0045] The additives include one or more of polyacrylamide, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, melamine-formaldehyde resin, acetic acid, and lithium acetate;

[0046] The water-soluble carbon source includes one or more of glucose, sucrose, maltodextrin, starch, povidone, and polyacrylic acid;

[0047] The sintering temperature is 550~800℃;

[0048] The sintering time is 4 to 6 hours.

[0049] The present invention also provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte;

[0050] The material of the negative electrode includes SiO as described in any one of the above technical solutions. x -M@CG composite anode material or SiO prepared by any of the above-mentioned technical solutions. x -M@CG composite anode material;

[0051] The negative electrode material does not contain a conductive agent.

[0052] This invention provides a SiO x -M@CG composite material, including: multiple SiO x -M@C particles; composite in one and / or multiple SiO2 particles x - Graphene sheets on M@C particles; wherein, 0.1 ≤ x ≤ 0.9; M is a metal and / or a metal salt; the plurality of SiO x -M@C particles, and / or, SiO x -M@C particles contain amorphous carbon between them and the graphene sheets; the SiO x -M@C particles include SiO x -M particles and coatings on SiO x - An amorphous carbon layer on the surface of M particles. Compared with existing technologies, this invention is based on research showing that silicon-oxygen composites have low initial efficiency and low conductivity, while metal doping can improve the initial efficiency and conductivity of the material. Simultaneously, composite graphene reduces the charge-discharge expansion rate of the composite material, improving its conductivity and cycle stability. Based on this, this invention provides a SiO₂ structure and composition with specific characteristics. x -M@CG composite material, composed of SiO₂ x -M@C particles are encased in a cage-like structure within graphene sheets. The structure is filled with M particles, and the particles contain porous structures, SiO... x -M@C particles and graphene sheets are connected by amorphous carbon to form SiO2. x -M@CG composite structure.

[0053] The SiO provided by this invention x -M@CG composite material, with SiO x -M is the substrate material, with metal M particles dispersed in SiO2. x In the particles; the SiO x -M is encapsulated with an amorphous carbon layer on the outside; the inner and outer layers are encapsulated with three-dimensional, spherical graphene microflakes. This composite material includes SiO2. x -M and two or more active materials, including graphene and amorphous carbon. In this composite material, the graphene composite three-dimensional structure can be SiO2. x - The volume expansion of M particles provides space, while the in-situ growth of amorphous carbon improves the electrical conductivity and structural stability of the composite material, reduces the volume expansion of the material during charging and discharging, and the graphene coating reduces the SiO2 content. x The increased contact surface between the M-type electrolyte and the composite material improves the stability of the SEI film, enhances the cycle efficiency and stability of the composite material, and the improved conductivity helps to maximize the rate performance of the composite material.

[0054] The SiO provided by this invention x The preparation process of the -M@CG composite material is simple, controllable, and mild, making it more suitable for industrial promotion and application. In the preparation process of this invention, the metal does not generate vapor in the low-temperature region, greatly improving reaction safety. This effectively solves the problems of existing methods for preparing similar silicon-based composite anode materials, which involve simultaneously evaporating SiO and metal into gas, mixing the gases, and then condensing them in the low-temperature region. These methods suffer from high energy consumption, safety risks associated with metal vapor preparation, and the different condensation temperatures of SiO and metal, leading to uncontrollable material composition, numerous impurities, and easy accumulation of condensed material in the pipelines. Furthermore, the equipment used has a dual-furnace, dual-temperature-zone control system, requiring specialized equipment design, which is time-consuming and labor-intensive. Using the silicon-carbon composite material provided by this invention as a lithium-ion battery composite material, the amorphous carbon-graphene composite structure and M metal doping can improve the conductivity of silicon oxide carbon particles, thereby increasing the battery rate performance. M metal doping can improve the first-pass yield of silicon oxide carbon and effectively suppress the volume expansion of SiO during charging and discharging. The amorphous carbon-graphene composite granulation structure is stable and can more effectively suppress silicon oxide carbon expansion.

[0055] Experimental results show that the SiO provided by this invention x -M@CG composite materials are assembled into 2032 button cells, with an initial discharge capacity of 1500~1700 mAh / g, a charge-discharge efficiency of 78%~86%, and a capacity retention rate of 93%~98% after 100 cycles. Attached Figure Description

[0056] Figure 1 The SiO provided by the present invention x A simplified structural diagram of the M@CG composite anode material;

[0057] Figure 2 The SiO provided by the present invention x A simplified structural diagram of the M@CG composite anode material;

[0058] Figure 3 The SiO prepared in Example 1 of this invention x SiO in -M@CG composite anode material products x SEM image of Mg particles;

[0059] Figure 4 The SiO prepared in Example 1 of this invention x SEM image of -Mg@C particles;

[0060] Figure 5 The SiO prepared in Example 1 of this invention xSEM image of the Mg@CG composite anode material product;

[0061] Figure 6 The SiO prepared in Example 1 of this invention x XRD pattern of Mg@CG composite anode material product;

[0062] Figure 7 The SiO prepared in Example 1 of this invention x -Mg@CG composite anode material and SiO prepared in Comparative Example 1 x Cyclic performance diagram of the CG composite negative electrode material electrode sheet;

[0063] Figure 8 The SiO prepared in Example 1 of this invention x -Mg@CG composite anode material and SiO prepared in Comparative Example 1 x Rate performance diagram of the CG composite negative electrode material electrode sheet;

[0064] Figure 9 The SiO prepared in Example 1 of this invention x Comparison of electrode sheet expansion between Mg@CG composite anode material and SiOx@CG composite anode material prepared in Comparative Example 1;

[0065] Figure 10 The SiO prepared in Example 2 of this invention x -XRD pattern of Al@CG composite anode material product;

[0066] Figure 11 The SiO prepared in Example 3 of this invention x -XRD pattern of Ag@CG composite anode material product;

[0067] Figure 12 The SiO prepared in Example 4 of this invention x -XRD pattern of Sn@CG composite anode material product. Detailed Implementation

[0068] To further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims.

[0069] There are no particular restrictions on the source of any raw materials used in this invention; they can be purchased from the market or prepared using conventional methods known to those skilled in the art.

[0070] There are no particular restrictions on the purity of any raw materials used in this invention. However, it is preferred to use analytical grade or conventional purity used in the preparation of lithium-ion battery anodes.

[0071] This invention provides a SiO x -M@CG composite material, including: multiple SiO x -M@C particles;

[0072] Composite in single and / or multiple SiO x Graphene sheets on M@C particles;

[0073] Where 0.1 ≤ x ≤ 0.9; M is a metal and / or a metal salt;

[0074] The plurality of SiO x -M@C particles, and / or, SiO x -Amorphous carbon is present between the M@C particles and the graphene sheets;

[0075] The SiO x -M@C particles include SiO x -M particles and coatings on SiO x -M Amorphous carbon layer on the surface of particles.

[0076] In this invention, 0.1≤x≤0.9, more preferably 0.2≤x≤0.7, and even more preferably 0.4≤x≤0.5.

[0077] In this invention, the composite material is preferably a composite material with three-dimensional spherical and / or ellipsoidal shape, having graphene microsheets encapsulated in the inner and outer layers, and more preferably a composite material with three-dimensional spherical or ellipsoidal shape, having graphene microsheets encapsulated in the inner and outer layers.

[0078] In this invention, the composite material is preferably a porous material.

[0079] In this invention, the specific surface area of ​​the composite material is preferably 2 to 6 m². 2 / g, more preferably 2.5~5.5 m 2 / g, more preferably 3~5 m 2 / g, more preferably 3.5~4.5 m 2 / g

[0080] In this invention, the pore size of the composite material is preferably 10~2μm, more preferably 9~3μm, more preferably 8~4μm, and even more preferably 7~5μm.

[0081] In this invention, the particle size of the composite material is preferably 8~50μm, more preferably 18~40μm, and even more preferably 28~30μm.

[0082] In this invention, the composite material contains SiO xThe preferred mass ratio of SiO₂, M, C, and graphene is 100:(1~6):(1~15):(5~50), more preferably 100:(3~4):(1~15):(5~50), even more preferably 100:(1~6):(6~10):(5~50), and even more preferably 100:(1~6):(1~15):(25~30). In this invention, the SiO₂... x The particle size is preferably 100nm~10μm, more preferably 80nm~30μm, and even more preferably 60nm~50μm.

[0083] In this invention, the number of graphene sheets preferably includes 1 to 30 layers, more preferably 6 to 25 layers, and even more preferably 11 to 20 layers.

[0084] In this invention, the thickness of the amorphous carbon layer is preferably 1~200nm, more preferably 40~160nm, and even more preferably 80~120nm.

[0085] In this invention, the SiO x -M@C particles preferably have a core-shell structure.

[0086] In this invention, the plurality of SiO x -M@C particles are preferably encapsulated in a cage-like structure encapsulated in graphene sheets.

[0087] In this invention, the SiO x -M@C particles are preferably multiple SiO2 particles. x -M particles form secondary particles, and an amorphous carbon layer coats the surface of the secondary particles.

[0088] In this invention, the metal element preferably includes one or more of aluminum, magnesium, tin, silver, germanium, sodium and nickel, and more preferably aluminum, magnesium, tin, silver, germanium, sodium or nickel.

[0089] In this invention, the secondary particles are preferably particles with pores on the surface and / or inside, and more preferably particles with pores on the surface or inside.

[0090] In this invention, the particle size of the secondary particles is preferably 1μm~20μm, more preferably 5μm~16μm, and even more preferably 9μm~12μm.

[0091] In this invention, the surface and / or internal pores preferably contain M particles.

[0092] In this invention, the SiO x -M preferably includes SiO x Complexes formed with metals, SiO x Complexes formed with metal salts and SiOx One or more of the complexes formed with metal silicates, more preferably SiO x Complexes formed with metals, SiO x Complexes formed with metal salts or SiO x Complexes formed with metal silicates.

[0093] In this invention, the SiO x Complexes formed with metals, SiO x Complexes formed with metal salts and SiO x The complexes formed with metal silicates preferably have one or more of the following connections: coating, doping, intercalation, and chemical bonding, and more preferably, coating, doping, intercalation, or chemical bonding.

[0094] In this invention, M is preferably doped in SiO. x Inside and on the surface of the particles.

[0095] In this invention, the plurality of SiO x -M@C particles, and / or, SiO x -M@C particles are preferably connected to graphene sheets via amorphous carbon.

[0096] In this invention, the amorphous carbon preferably has a framework structure.

[0097] In this invention, the composite material is preferably a negative electrode active material.

[0098] In this invention, the silicon-based active material preferably accounts for more than 60% of the total mass of the composite material, more preferably more than 63%, and even more preferably more than 65%. Specifically, the silicon-based active material refers to the silicon-containing substances in the composite material, and the total active material is the composite material itself.

[0099] This invention aims to better complete and refine the overall technical solution, and to better guarantee the SiO2 production process. x -The structure and specific composition of the M@CG composite material further improve SiO x The electrochemical properties and stability of the -M@CG composite material, wherein the SiO x -M@CG composite materials can specifically have the following structures:

[0100] The SiO provided by this invention x -M@CG composite anode materials, including SiO x -M@C matrix;

[0101] SiO x -M is the substrate material; the SiOx -M is encapsulated with an amorphous carbon layer on the outside; the inner and outer layers are encapsulated with three-dimensional spherical graphene microflakes.

[0102] This composite material includes SiO₂ x -M and two or more active substances, including graphene and amorphous carbon;

[0103] The negative electrode active material contains SiO x -M active material and graphene-based active material, the SiO x -M active material is composed of M doped inside and on the surface of SiOx particles, where SiO x The ratio satisfies 0.1≤X≤0.9; the silicon-based active material accounts for more than 60% of the total active material mass.

[0104] Filled in SiO x -M@CG composite material contains SiO x -M particles and graphene sheets, amorphous carbon;

[0105] Connecting SiO x -M@C and graphene amorphous carbon layers.

[0106] Specifically, the SiO x The specific surface area of ​​the -M@CG composite anode material is 2~6 m². 2 / g, pore size 10nm~2μm, particle size 8μm~50μm.

[0107] Specifically, the SiO x -M@CG composite anode material SiO x The mass ratio of M, C, and graphene is 100:1~6:1~15:5~50.

[0108] Specifically, the SiO x The particle size is 100nm~10μm.

[0109] The SiO provided by this invention x -M@CG composite anode material is made of SiO₂ x -M@C particles are encased in a cage-like structure within graphene sheets. The structure is filled with M particles, and the particles contain porous structures, SiO... x -M@C particles and graphene sheets are connected by amorphous carbon to form SiO2. x -M@CG composite structure. This composite material uses SiO2. x -M is the substrate material, with metal M particles dispersed in SiO2. x In the particles; the SiO x-M is encapsulated by an amorphous carbon layer; the inner and outer layers are encapsulated with three-dimensional, spherical graphene microflakes. The composite material includes SiO2. x -M and two or more active materials, including graphene and amorphous carbon. The SiO provided by this invention... x In -M@CG composite materials, the graphene composite three-dimensional structure can provide SiO2 x - The volume expansion of M particles provides space, while the in-situ growth of amorphous carbon improves the electrical conductivity and structural stability of the composite material, reduces the volume expansion of the material during charging and discharging, and the graphene coating reduces the SiO2 content. x The increased contact surface between the M-type electrolyte and the composite material improves the stability of the SEI film, enhances the cycle efficiency and stability of the composite material, and the improved conductivity helps to maximize the rate performance of the composite material.

[0110] This invention provides a SiO x The preparation method of -M@CG composite material includes the following steps:

[0111] 1) After mixing SiO2 and Si, a powder mixture is obtained. This powder mixture is then subjected to vacuum high-temperature treatment to form SiO2. x Gas, then SiO x Gas is introduced into a vacuum low-temperature zone containing M metal powder and / or M metal salt, SiO x The gas is passed through a device containing M metal powder and / or M metal salt to obtain SiO. x -M precursor;

[0112] 2) Under protective gas conditions, the SiO2 obtained in the above steps is... x - After heating the M precursor, a carbon-containing reaction gas is introduced, and after chemical vapor deposition, SiO is obtained. x -M@C materials;

[0113] 3) The SiO obtained in the above steps x -M@C materials, dispersants, additives, water-soluble carbon sources, and graphene aqueous dispersions are mixed and then granulated to obtain SiO2. x -M@CG precursor, then sintered under a protective atmosphere to obtain SiO x -M@CG composite material.

[0114] This invention first mixes SiO2 and Si to obtain a powder mixture, which is then subjected to vacuum high-temperature treatment to form SiO2. x Gas, then SiO x Gas is introduced into a vacuum low-temperature zone containing M metal powder and / or M metal salt, SiO x The gas is passed through a device containing M metal powder and / or M metal salt to obtain SiO.x -M precursor.

[0115] In this invention, the vacuum pressure of the high-temperature vacuum is preferably 0.01~100 Pa, more preferably 0.1~80 Pa, more preferably 1~60 Pa, more preferably 5~40 Pa, and even more preferably 15~20 Pa.

[0116] In this invention, the vacuum high temperature is preferably 1300~1500℃, more preferably 1340~1460℃, and even more preferably 1380~1420℃.

[0117] In this invention, the vacuum high-temperature treatment time is preferably 5-10 hours, more preferably 6-9 hours, and even more preferably 7-8 hours.

[0118] In this invention, the vacuum cryogenic temperature is preferably 300~500℃, more preferably 340~460℃, and even more preferably 380~420℃.

[0119] In this invention, the SiO x The preferred D50 particle size of the -M precursor is 100 nm to 10 μm, more preferably 500 nm to 1600 nm, and even more preferably 900 nm to 1200 nm.

[0120] The present invention further processes the SiO2 obtained in the above steps under protective gas conditions. x - After heating the M precursor, a carbon-containing reaction gas is introduced, and after chemical vapor deposition, SiO is obtained. x -M@C material.

[0121] Finally, the SiO obtained in the above steps is used in this invention. x -M@C materials, dispersants, additives, water-soluble carbon sources, and graphene aqueous dispersions are mixed and then granulated to obtain SiO2. x -M@CG precursor, then sintered under a protective atmosphere to obtain SiO x -M@CG composite material.

[0122] In this invention, the dispersant preferably includes one or more of polyethylene glycol, polyacryl alcohol, Tween-60, Tween-80, sodium dodecyl sulfonate, and sodium dodecyl sulfate, more preferably polyethylene glycol, polyacryl alcohol, Tween-60, Tween-80, sodium dodecyl sulfonate, or sodium dodecyl sulfate.

[0123] In this invention, the additive preferably includes one or more of polyacrylamide, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, melamine-formaldehyde resin, acetic acid, and lithium acetate, and more preferably polyacrylamide, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, melamine-formaldehyde resin, acetic acid, or lithium acetate.

[0124] In this invention, the water-soluble carbon source preferably includes one or more of glucose, sucrose, maltodextrin, starch, povidone, and polyacrylic acid, and more preferably glucose, sucrose, maltodextrin, starch, povidone, or polyacrylic acid.

[0125] In this invention, the sintering temperature is preferably 550~800℃, more preferably 590~760℃, more preferably 630~720℃, and even more preferably 670~680℃.

[0126] In this invention, the sintering time is preferably 4 to 6 hours, more preferably 4.4 to 5.6 hours, and even more preferably 4.8 to 5.2 hours.

[0127] This invention aims to better complete and refine the overall technical solution, and to better guarantee the SiO2 production process. x -The structure and specific composition of the M@CG composite material further improve SiO x The electrochemical properties and stability of the -M@CG composite material, wherein the SiO x The preparation method of -M@CG composite material can be specifically described by the following steps:

[0128] (1) SiO x -M precursor preparation process: SiO2 bulk material is mixed with Si bulk material in a certain proportion, and the mixture is processed into coarse powder and fine powder to obtain a powder material, resulting in a mixture. After compaction, the mixture is placed in a crucible, which is then placed in the high-temperature zone of a vacuum furnace. A crucible containing a certain amount of M metal powder or M salt is placed in the low-temperature zone of the vacuum furnace. The vacuum furnace is evacuated, and the mixture is held at a certain reaction temperature for an appropriate time. The SiO gas generated by the reaction is introduced into the low-temperature zone of the vacuum furnace and condensed in the crucible containing a certain amount of M metal powder or M salt to obtain flake or block SiO. x -M material; SiO2 in sheet or block form x -M material is processed into SiO₂ of a certain size through coarse powder and air jet milling. x -M precursor.

[0129] There are no special restrictions on the source of the raw material components used in the SiO2 bulk material, Si bulk material, M metal powder, or M salt; they can be commercially available.

[0130] (2) SiO x -M@C preparation process: SiO2 x The -M precursor is placed in the reactor and heated to a certain temperature under a protective gas. The protective gas is then stopped, and a carbon-containing reactive gas is introduced for chemical vapor deposition to obtain SiO2. x -M@C.

[0131] (3) SiOx -M@CG preparation process: A certain amount of SiO2 is added... x -M@C materials, dispersants, additives, water-soluble carbon sources, and graphene slurry are uniformly dispersed and mixed, dried, and granulated to obtain SiO2. x -M@CG precursor.

[0132] The raw material components used in the graphene slurry are not subject to any special restrictions and can be commercially available; after sintering in an inert atmosphere, sieving, and iron removal, a SiO2 is obtained. x -M@CG composite anode material.

[0133] Specifically, the graphene sheets have a diameter of 200 nm to 20 μm and 1 to 30 layers. The graphene can be prepared by intercalation exfoliation, oxidative exfoliation, mechanical exfoliation, or other methods.

[0134] Specifically, the drying and granulation methods include methods such as stirring and evaporation, centrifugal drying, two-flow drying, and flash drying.

[0135] Specifically, the vacuum degree is 0.01~100 Pa, the reaction temperature is 1300~1500℃, and the heat preservation time is 5~10 h.

[0136] Specifically, the M metal powder or M salt mentioned above, the M element includes one or more of aluminum, magnesium, tin, silver, germanium, sodium, and nickel.

[0137] More specifically,

[0138] SiO x The preparation method for -M@CG composite materials can also include the following steps:

[0139] (1) SiO x -M precursor preparation process: SiO2 bulk material is mixed with Si bulk material in a certain proportion, and the mixture is processed into coarse powder and fine powder to obtain a powder material, resulting in a mixture. After compaction, the mixture is placed in a crucible, which is then placed in the high-temperature zone of a vacuum furnace. A crucible containing a certain amount of M metal powder or M salt is placed in the low-temperature zone of the vacuum furnace. The vacuum furnace is evacuated to 0.01~100 Pa, and the temperature is increased to 1300-1500℃ at a rate of 5~20℃ per minute, and held for 5~10 hours. The SiO gas generated by the reaction of the material is introduced into the low-temperature zone of the vacuum furnace and condensed in the crucible containing a certain amount of M metal powder or M salt to obtain flake or block SiO. x -M material; SiO2 in sheet or block form x -M material was subjected to coarse powder and air jet milling to obtain SiO₂ with a D50 of 100nm~10μm. x -M precursor.

[0140] There are no special restrictions on the source of the raw material components used in the SiO2 bulk material, Si bulk material, M metal powder, or M salt; they can be commercially available.

[0141] (2) SiO x -M@C preparation process: SiO2 x The -M precursor is placed in the reactor and heated to a certain temperature under a protective gas. The protective gas is then stopped, and a carbon-containing reactive gas is introduced for chemical vapor deposition to obtain SiO2. x -M@C.

[0142] (3) SiO x -M@CG preparation process: A certain amount of SiO2 is added... x -M@C materials, dispersants, additives, carbon sources, and graphene slurry are uniformly dispersed and mixed, dried, and granulated to obtain SiO2. x -M@CG precursor. After sintering in an inert atmosphere, sieving, and iron removal, a SiO₂ precursor is obtained. x -M@CG composite anode material.

[0143] The raw material components used in the graphene slurry are not subject to any special restrictions and can be commercially available.

[0144] See Figure 1 , Figure 1 The SiO provided by the present invention x A simplified structural diagram of the -M@CG composite anode material. Where 1 represents SiO₂. x -M@C particles, 2 is graphene sheet.

[0145] See Figure 2 , Figure 2 The SiO provided by the present invention x - A simplified structural diagram of the M@CG composite anode material. Wherein, 1-1 represents SiO₂. x @M y SiO z -C particles, 1-2 are amorphous carbon layers, 1-3 are M metal particles, and 1-4 are the porous structure in the particles.

[0146] In this invention, SiO x -M@C particles 1 are encased in a cage-like structure within graphene sheets 2. Within this structure, particles 1-3 are M particles, and particles 1-4 are porous structures within the particles. (SiO2) x There are amorphous carbon connections between M@C particles 1 and graphene sheets 2.

[0147] The three-dimensional structure in this invention can be SiO2-containing x The particles expand in volume during charging and discharging, providing space, and the surface M y SiOz The amorphous carbon coating reduces the contact area between the negative electrode material and the electrolyte, which is conducive to the rapid exchange of lithium ions at the contact area and has good cycle stability. The doping of M metal particles and the composite coating of graphene improve the electronic conductivity of the material.

[0148] The SiO provided by this invention x -M@CG composite anode materials are ellipsoidal or near-spherical in shape.

[0149] The present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte.

[0150] The material of the negative electrode includes SiO as described in any one of the above technical solutions. x -M@CG composite anode material or SiO prepared by any of the above-mentioned technical solutions. x -M@CG composite anode material;

[0151] The negative electrode material does not contain a conductive agent.

[0152] In this invention, the lithium-ion battery is a lithium-ion battery without a conductive agent. Specifically, the negative electrode does not contain a conductive agent. That is, the negative electrode material of the lithium-ion battery in this invention does not require a conductive agent. The positive electrode is not particularly limited.

[0153] The lithium-ion battery described in this invention may specifically include a positive electrode, a negative electrode, a separator, an electrolyte, and a casing.

[0154] The present invention provides a SiO x -M@CG composite material and its preparation method, lithium-ion battery. This silicon-carbon composite material has a specific structure and composition, consisting of SiO2. x -M@C particles are encased in a cage-like structure within graphene sheets. The structure is filled with M particles, and the particles contain porous structures, SiO... x -M@C particles and graphene sheets are connected by amorphous carbon to form SiO2. x -M@CG composite structure.

[0155] The SiO provided by this invention x -M@CG composite material, with SiO x -M is the substrate material, and metal M particles are dispersed in SiOx particles; the SiO... x -M is encapsulated with an amorphous carbon layer on the outside; the inner and outer layers are encapsulated with three-dimensional, spherical graphene microflakes. This composite material includes SiO2. x -M and two or more active materials, including graphene and amorphous carbon. In this composite material, the graphene composite three-dimensional structure can be SiO2. x- The volume expansion of M particles provides space, while the in-situ growth of amorphous carbon improves the electrical conductivity and structural stability of the composite material, reduces the volume expansion of the material during charging and discharging, and the graphene coating reduces the SiO2 content. x The increased contact surface between the M-type electrolyte and the composite material improves the stability of the SEI film, enhances the cycle efficiency and stability of the composite material, and the improved conductivity helps to maximize the rate performance of the composite material.

[0156] The SiO provided by this invention x The preparation process of the -M@CG composite material is simple, controllable, and mild, making it more suitable for industrial promotion and application. In the preparation process of this invention, the metal does not generate vapor in the low-temperature region, greatly improving reaction safety. This effectively solves the problems of existing methods for preparing similar silicon-based composite anode materials, which involve simultaneously evaporating SiO and metal into gas, mixing the gases, and then condensing them in the low-temperature region. These methods suffer from high energy consumption, safety risks associated with metal vapor preparation, and the different condensation temperatures of SiO and metal, leading to uncontrollable material composition, numerous impurities, and easy accumulation of condensed material in the pipelines. Furthermore, the equipment used has a dual-furnace, dual-temperature-zone control system, requiring specialized equipment design, which is time-consuming and labor-intensive. Using the silicon-carbon composite material provided by this invention as a lithium-ion battery composite material, the amorphous carbon-graphene composite structure and M metal doping can improve the conductivity of silicon oxide carbon particles, thereby increasing the battery rate performance. M metal doping can improve the first-pass yield of silicon oxide carbon and effectively suppress the volume expansion of SiO during charging and discharging. The amorphous carbon-graphene composite granulation structure is stable and can more effectively suppress silicon oxide carbon expansion.

[0157] Experimental results show that the SiO provided by this invention x -M@CG composite materials are assembled into 2032 button cells, with an initial discharge capacity of 1500~1700 mAh / g, a charge-discharge efficiency of 78%~86%, and a capacity retention rate of 93%~98% after 100 cycles.

[0158] To further illustrate the present invention, the following embodiments describe a SiO2 provided by the present invention. x The -M@CG composite material and its preparation method, as well as lithium-ion batteries, are described in detail. However, it should be understood that these embodiments are implemented under the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given only to further illustrate the features and advantages of the present invention, and are not intended to limit the scope of the claims of the present invention. The scope of protection of the present invention is not limited to the following embodiments.

[0159] Example 1 and Comparative Example 1

[0160] Coarse SiO2 particles and coarse Si particles are pulverized in a pulverizer at a speed of 800-1800 rpm. The pulverized material is then pulverized in an air jet mill for 0.5-1 hour, followed by pulverization in an air jet mill classifier at a speed of 500-2000 rpm. The preferred air pressure is 0.4-1.2 MPa. The resulting SiO2 particles have a diameter of 1 μm-30 μm. x Mixed powders.

[0161] 2kg SiO x The mixed powder is placed in a crucible and then placed in the high-temperature zone of a vacuum furnace. A certain amount of metallic Mg or magnesium salt is placed in the crucible and then placed in the low-temperature zone of the vacuum furnace. The vacuum furnace is evacuated to -10 to 10 Pa, and the temperature is increased to 1300 to 1500°C at a rate of 5 to 20°C per minute, and held for 5 to 10 hours. The SiO gas generated by the reaction of the materials reacts with metallic Mg or magnesium salt in the low-temperature zone, and the resulting SiO gas condenses in the crucible to obtain flake or block-shaped SiO. x -Mg materials; SiO2 in flake or block form x -Mg material was coarsely ground and then air-jet milled to obtain SiO₂ with a D50 of 100nm~10μm. x -Mg precursor.

[0162] 2kgSiO x -Mg precursor, 100g dispersant, 500g carbon source, and 20kg graphene slurry were mixed evenly and then spray-dried for granulation. The inlet temperature of the dryer was 220℃, and the outlet temperature was 90℃. The obtained SiO x The Mg@CG precursor was then placed in an atmosphere furnace, and under inert gas protection, the furnace temperature was raised to 700℃ and held for 5 hours. After cooling to room temperature, SiO2 was obtained by sieving and removing iron. x -Mg@CG composite anode material.

[0163] According to the above scheme, SiO will be obtained x Precursor Substitute for SiO x SiO was prepared from Mg precursor. x @CG composite anode material, as comparative example 1.

[0164] The SiO prepared in Example 1 of this invention x The Mg@CG composite anode material was characterized.

[0165] SiO x The composition of the Mg@CG composite anode material was analyzed using a TG thermogravimetric analyzer. Different temperatures and heating methods were used to analyze and quantify the C and graphene components in the material. ICP was used to analyze and quantify the M element.

[0166] See Figure 3 , Figure 3 The SiO prepared in Example 1 of this invention x SiO in -M@CG composite anode material products x -SEM image of Mg particles.

[0167] from Figure 3 As can be seen from this, SiO x -Mg particles are irregularly shaped micron-sized particles with pores on their surface and inside, ranging in size from 1 μm to 20 μm. These particles are composed of even smaller nano and micron-sized particles. SiO x The surface is coated with a layer of MgSiO3, and both the surface and the interior are filled with nano-M particles.

[0168] See Figure 4 , Figure 4 The SiO prepared in Example 1 of this invention x SEM image of -Mg@C particles.

[0169] from Figure 4 SiO x The SEM image of Mg@C particles shows that SiO x The Mg surface is coated with a layer of amorphous carbon, with a thickness of 1~200nm, and there are also some free SiO2 on the surface. x -Mg@C particles, connected by amorphous carbon layers.

[0170] See Figure 5 , Figure 5 The SiO prepared in Example 1 of this invention x SEM image of the Mg@CG composite anode material product.

[0171] from Figure 5 As can be seen from this, SiO x -Mg@CG composite anode material is spherical, with graphene and amorphous carbon encapsulating both the interior and surface of the particles. The particle size ranges from 8μm to 50μm, and it contains pores ranging from 10nm to 2μm in size and micrometers. SiO x - A uniform layer of amorphous C is coated on the surface of Mg, with a thickness of 2-200 nm. The C content in the composite material is 2-15%, the Mg content is 1-5%, and the G content is 8-30%.

[0172] See Figure 6 , Figure 6 The SiO prepared in Example 1 of this invention x XRD pattern of Mg@CG composite anode material product.

[0173] In the figure, 2θ is the characteristic peak of graphene at 26.59°, the characteristic peaks of Si at 28.4°, 47.3°, and 56.1°, the characteristic peaks of MgSiO3 at 28.1°, 28.3°, 31.1°, 62.5°, and 63.2°, and the characteristic peaks of Mg at 32.1°, 34.4°, and 36.6°. As can be seen... Figure 6 Magnesium silicate was generated in the XRD, which means that the tetravalent SiO2 in the silicon oxide was reacted away, reducing the O content in the silicon oxide itself.

[0174] The SiO prepared in Example 1 of this invention x @CG composite anode material and SiO x Electrochemical performance testing was conducted on the Mg@CG composite anode material.

[0175] The fabrication and electrochemical performance testing of the 2030 button cell were as follows: The mass ratio of composite negative electrode material, carbon black, and CMC+SBR was 80:10:10. The composite negative electrode material and carbon black were mixed evenly, and then an aqueous solution of CMC+SBR was added. The mixture was coated onto Cu foil and vacuum dried at 120℃ for 24 hours in a vacuum drying oven. An electrode sheet with a diameter of 1.6 cm was used as the working electrode, and a lithium metal sheet was used as the counter electrode. The electrolyte was LiPF6 / EC-DMC-EMC (volume ratio 1:1:1). The 2032 button cell was assembled in a glove box filled with Ar gas. The charge / discharge voltage range was 2.0~0.005V, the first charge / discharge current was 200mA / g (0.1C), and the charge / discharge current density thereafter was 400mA / g (0.2C).

[0176] In the battery manufacturing process, SiO x The electrode thickness of the Mg@CG composite anode material was tested using an electronic micrometer after coating, rolling, standing for 2 hours, liquid absorption, 50% lithium intercalation, and 100% lithium intercalation.

[0177] According to tests, SiO x The Mg@CG composite anode material exhibits an initial discharge capacity of 1693.6 mAh / g and a charge-discharge efficiency of 84.2%. After 100 cycles, the capacity retention is 95%. The delithiation capacity at 0.2C is 1495.6 mAh / g, at 0.5C it is 1351.2 mAh / g, at 1C it is 1202.4 mAh / g, and at 2C it is 956.2 mAh / g. (SiO2) xThe @CG composite anode material exhibits an initial discharge capacity of 1994.2 mAh / g and a charge-discharge efficiency of 76.0%. After 100 cycles, the capacity retention rate is 93%. The delithiation capacity at 0.2C rate is 1404.5 mAh / g, at 0.5C rate is 1262.0 mAh / g, at 1C rate is 1050.4 mAh / g, and at 2C rate is 801.3 mAh / g.

[0178] See Figure 7 , Figure 7 The SiO prepared in Example 1 of this invention x -Mg@CG composite anode material and SiO prepared in Comparative Example 1 x Cyclic performance diagram of the CG composite negative electrode material.

[0179] See Figure 8 , Figure 8 The SiO prepared in Example 1 of this invention x -Mg@CG composite anode material and SiO prepared in Comparative Example 1 x Rate performance diagram of the @CG composite negative electrode material electrode sheet.

[0180] Depend on Figure 7 and 8 It can be seen that SiO x -Mg@CG composite anode materials exhibit superior cycle stability and rate performance.

[0181] See Figure 9 , Figure 9 The SiO prepared in Example 1 of this invention x -Mg@CG composite anode material and SiO prepared in Comparative Example 1 x @CG composite negative electrode material electrode sheet expansion phase comparison diagram.

[0182] Depend on Figure 9 It can be seen that the electrode expands after coating, expands after rolling, expands after battery assembly, and the electrode expansion rate after 100% charging, SiO x -Mg@CG composite anode material is superior to SiO x @CG composite negative electrode material has a small expansion rate after assembly and after being fully charged.

[0183] Example 2

[0184] 2kg SiO xThe mixed powder is placed in a crucible and then placed in the high-temperature zone of a vacuum furnace. A certain amount of metallic Al or metallic aluminum salt is placed in the crucible and then placed in the low-temperature zone of the vacuum furnace. The vacuum furnace is evacuated to -10 to 10 Pa, and the temperature is increased to 1300 to 1500°C at a rate of 5 to 20°C per minute, and held for 5 to 10 hours. The SiO gas generated by the reaction of the materials reacts with metallic Al or metallic aluminum salt in the low-temperature zone, and condenses in the crucible to obtain flake or block SiO. x -Al material; SiO2 in sheet or block form x -Al material is coarsely ground and then air-jet milled to obtain SiO₂ with a D50 of 100nm~10μm. x -Al precursor.

[0185] The obtained SiO x The Al precursor was then placed in an atmosphere furnace, and the furnace temperature was raised to 700°C under a nitrogen protective atmosphere. Then, 15 L of acetylene gas was uniformly introduced into the furnace over 5 hours while simultaneously stopping the nitrogen supply. Afterward, nitrogen protection was introduced, and the furnace was cooled to room temperature. The resulting product was then sieved and iron-removed to obtain SiO₂. x -Al@C material.

[0186] 2kgSiO x Al@C material, 100g dispersant, 100g additive, and 15kg graphene slurry were mixed evenly and then spray-dried for granulation. The inlet temperature of the dryer was 220℃, and the outlet temperature was 90℃. The resulting SiO₂... x The Mg@CG precursor was then placed in an atmosphere furnace, and under inert gas protection, the furnace temperature was raised to 750℃ and held for 5 hours. After cooling to room temperature, SiO2 was obtained by sieving and iron removal. x -Al@CG composite anode material.

[0187] According to tests, SiO x The Al@CG composite anode material has an initial discharge capacity of 1750.1 mAh / g, a charge-discharge efficiency of 81%, and a capacity retention rate of 93% after 100 cycles.

[0188] The SiO2 prepared in Example 2 of this invention x The Al@CG composite anode material was characterized.

[0189] See Figure 10 , Figure 10 The SiO prepared in Example 2 of this invention x -XRD pattern of Al@CG composite anode material product.

[0190] from Figure 10 As can be seen in the XRD pattern, 2θ is a characteristic peak of Al at 38.5°, 44.7°, and 65.1°.

[0191] Example 3

[0192] 2kg SiO x The mixed powder is placed in a crucible and then placed in the high-temperature zone of a vacuum furnace. A certain amount of metallic Ag or metallic silver salt is placed in the crucible and then placed in the low-temperature zone of the vacuum furnace. The vacuum furnace is evacuated to -10 to 10 Pa, and the temperature is increased to 1300 to 1500°C at a rate of 5 to 20°C per minute, and held for 5 to 10 hours. The SiO gas generated by the reaction of the materials reacts with metallic Ag or metallic silver salt in the low-temperature zone, and the resulting SiO gas condenses in the crucible to obtain flake or block-shaped SiO. x -Ag material; SiO2 in sheet or block form x -Ag material was coarsely ground and then air-jet milled to obtain SiO₂ with a D50 of 100nm~10μm. x -Ag precursor.

[0193] 2kgSiO x - Ag precursor, 100g dispersant, 600g carbon source, and 15kg graphene slurry were mixed evenly and then spray-dried for granulation. The inlet temperature of the dryer was 220℃, and the outlet temperature was 90℃. The obtained SiO x The Mg@CG precursor was then placed in an atmosphere furnace, and under inert gas protection, the furnace temperature was raised to 700℃ and held for 5 hours. After cooling to room temperature, SiO2 was obtained by sieving and removing iron. x -Ag@CG composite anode material.

[0194] According to tests, SiO x The Ag@CG composite anode material has an initial discharge capacity of 1542.5 mAh / g, a charge-discharge efficiency of 78%, and a capacity retention rate of 96% after 100 cycles.

[0195] The SiO prepared in Example 3 of this invention x The Ag@CG composite anode material was characterized.

[0196] See Figure 11 , Figure 11 The SiO prepared in Example 3 of this invention x -XRD pattern of Ag@CG composite anode material product.

[0197] from Figure 11 As can be seen in the XRD pattern, 2θ is the characteristic peak of Ag at 38.1°, 44.3°, 64.4°, and 77.5°.

[0198] Example 4

[0199] 2kg SiO xThe mixed powder is placed in a crucible and then placed in the high-temperature zone of a vacuum furnace. A certain amount of metallic Sn or metallic tin salt is placed in the crucible and then placed in the low-temperature zone of the vacuum furnace. The vacuum furnace is evacuated to -10 to 10 Pa, and the temperature is increased to 1300 to 1500°C at a rate of 5 to 20°C per minute, and held for 5 to 10 hours. The SiO gas generated by the reaction of the materials reacts with metallic Sn or metallic tin salt in the low-temperature zone, and the gas condenses in the crucible to obtain flake or block SiO. x -Sn material; SiO2 in sheet or block form x -Sn material is coarsely ground and then air-jet milled to obtain SiO₂ with a D50 of 100nm~10μm. x -Sn precursor.

[0200] 2kgSiO x Sn precursor, 100g dispersant, 600g carbon source, and 15kg graphene slurry were mixed evenly and then spray-dried for granulation. The inlet temperature of the dryer was 220℃, and the outlet temperature was 90℃. The obtained SiO x The Sn@CG precursor was placed in an atmosphere furnace, and under inert gas protection, the furnace temperature was raised to 600℃ and held for 5 hours. After cooling to room temperature, SiO2 was obtained by sieving and removing iron. x -Sn@CG composite anode material.

[0201] According to tests, SiO x The Sn@CG composite anode material has an initial discharge capacity of 1603.4 mAh / g, a charge-discharge efficiency of 82%, and a capacity retention rate of 94% after 100 cycles.

[0202] The SiO prepared in Example 4 of this invention x -The Sn@CG composite anode material was characterized.

[0203] See Figure 12 , Figure 12 The SiO prepared in Example 4 of this invention x -XRD pattern of Sn@CG composite anode material product.

[0204] from Figure 12 As can be seen in the XRD pattern, 2θ is a characteristic peak of Sn at 30.6°, 32.0°, 43.8°, and 44.9°.

[0205] Example 5

[0206] 2kg SiO xThe mixed powder is placed in a crucible and then placed in the high-temperature zone of a vacuum furnace. A certain amount of metallic Mg or magnesium salt is placed in the crucible and then placed in the low-temperature zone of the vacuum furnace. The vacuum furnace is evacuated to -10 to 10 Pa, and the temperature is increased to 1300 to 1500°C at a rate of 5 to 20°C per minute, and held for 5 to 10 hours. The SiO gas generated by the reaction of the materials reacts with metallic Mg or magnesium salt in the low-temperature zone, and the resulting SiO gas condenses in the crucible to obtain flake or block-shaped SiO. x -Mg materials; SiO2 in flake or block form x -Mg material was coarsely ground and then air-jet milled to obtain SiO₂ with a D50 of 100nm~10μm. x -Mg precursor.

[0207] The obtained SiO x The Mg precursor was then placed in an atmosphere furnace, and the furnace temperature was raised to 600°C under a nitrogen protective atmosphere. Then, 15 L of acetylene gas was uniformly introduced into the furnace over 5 hours while simultaneously stopping the nitrogen supply. Afterward, nitrogen protection was introduced, and the furnace was cooled to room temperature. The resulting product was then sieved and iron-removed to obtain SiO₂. x -Mg@C material.

[0208] 2kgSiO x -Mg@C material, 100g dispersant, 100g additive, and 15kg graphene slurry were mixed evenly and then spray-dried for granulation. The inlet temperature of the dryer was 220℃, and the outlet temperature was 90℃. The obtained SiO x The Mg@CG precursor was then placed in an atmosphere furnace, and under inert gas protection, the furnace temperature was raised to 600℃ and held for 5 hours. After cooling to room temperature, SiO2 was obtained by sieving and removing iron. x -Mg@CG composite anode material.

[0209] According to tests, SiO x The -Mg@CG composite anode material has an initial discharge capacity of 1607.5 mAh / g, a charge-discharge efficiency of 84%, and a capacity retention rate of 98% after 100 cycles.

[0210] The above describes a SiO2 provided by the present invention. xThe invention provides a detailed description of the M@CG composite material, its preparation method, and lithium-ion batteries. Specific examples are used to illustrate the principles and implementation methods of the invention. The descriptions of these embodiments are merely to aid in understanding the methods and core ideas of the invention, including the best mode, and to enable any person skilled in the art to practice the invention, including manufacturing and using any device or system, and implementing any combined method. It should be noted that those skilled in the art can make various improvements and modifications to the invention without departing from its principles, and these improvements and modifications also fall within the scope of protection of the claims. The scope of protection of this patent is defined by the claims and may include other embodiments conceived by those skilled in the art. If these other embodiments have structural elements that are not different from the wording of the claims, or if they include equivalent structural elements that are not substantially different from the wording of the claims, then these other embodiments should also be included within the scope of the claims.

Claims

1. A SiO x -M@CG composite material, characterized in that, include: Multiple SiO x -M@C particles; Composite in single and / or multiple SiO x Graphene sheets on M@C particles; Where 0.1 ≤ x ≤ 0.9; M is a metal; The M-doped SiO x The interior and surface of the particles; The plurality of SiO x Between -M@C particles, and, SiO x -Amorphous carbon is present between the M@C particles and the graphene sheets; The SiO x -M@C particles include SiO x -M particles and coatings on SiO x -M Particle surface amorphous carbon layer; The SiO x -M@C particles specifically consist of multiple SiO2 particles. x -M particles form secondary particles, and an amorphous carbon layer coats the surface of the secondary particles; The plurality of SiO x -M@C particles are encased in a cage-like structure within graphene sheets; The plurality of SiO x Between -M@C particles, and, SiO x -M@C particles are connected to graphene sheets through amorphous carbon; The amorphous carbon has a framework structure; The SiO x The preparation method of -M@CG composite material includes the following steps: 1) After mixing SiO2 and Si, a powder mixture is obtained. This powder mixture is then subjected to vacuum high-temperature treatment to form SiO2. x Gas, then SiO x Gas is introduced into a vacuum low-temperature zone containing M metal powder, SiO x The gas is passed through a device containing M metal powder to produce SiO. x -M precursor; The temperature of the vacuum cryogenic zone is 300~500℃; 2) Under protective gas conditions, the SiO2 obtained in the above steps is... x - After heating the M precursor, a carbon-containing reaction gas is introduced, and after chemical vapor deposition, SiO is obtained. x -M@C materials; 3) The SiO obtained in the above steps x -M@C materials, dispersants, additives, water-soluble carbon sources, and graphene aqueous dispersions are mixed and then granulated to obtain SiO2. x -M@CG precursor, then sintered under a protective atmosphere to obtain SiO x -M@CG composite material; The additives include one or more of polyacrylamide, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, melamine-formaldehyde resin, acetic acid, and lithium acetate.

2. The composite material according to claim 1, characterized in that, The composite material is a three-dimensional spherical and / or ellipsoidal composite material with graphene microflakes encapsulated in the inner and outer layers. The composite material is a porous material; The specific surface area of ​​the composite material is 2~6 m². 2 / g; The pore size of the composite material is 10~2μm; The particle size of the composite material is 8~50μm.

3. The composite material according to claim 1, characterized in that, The composite material contains SiO x The mass ratio of M, C to graphene is 100:(1~6):(1~15):(5~50); The SiO x The particle size is 100 nm to 10 μm; The graphene sheet diameter is 200 nm to 20 μm; The number of graphene sheets includes 1 to 30 layers; The thickness of the amorphous carbon layer is 1~200 nm.

4. The composite material according to claim 1, characterized in that, The SiO x -M@C particles have a core-shell structure; The metal includes one or more of the elements aluminum, magnesium, tin, silver, germanium, sodium, and nickel.

5. The composite material according to claim 4, characterized in that, The secondary particles are particles with pores on their surface and / or inside; The particle size of the secondary particles is 1μm~20μm; The SiO x -M includes SiO x Complexes formed with metals; The SiO x The complexes formed with metals have one or more of the following connections: coating, doping, intercalation, and chemical bonding.

6. The composite material according to claim 4, characterized in that, The composite material is a negative electrode active material; In the composite material, silicon-based active materials account for more than 60% of the total mass of the composite material.

7. A SiO as described in any one of claims 1 to 6 x The preparation method of -M@CG composite material is characterized by, Includes the following steps: 1) After mixing SiO2 and Si, a powder mixture is obtained. This powder mixture is then subjected to vacuum high-temperature treatment to form SiO2. x Gas, then SiO x Gas is introduced into a vacuum low-temperature zone containing M metal powder, SiO x The gas is passed through a device containing M metal powder to produce SiO. x -M precursor; The temperature of the vacuum cryogenic zone is 300~500℃; 2) Under protective gas conditions, the SiO2 obtained in the above steps is... x - After heating the M precursor, a carbon-containing reaction gas is introduced, and after chemical vapor deposition, SiO is obtained. x -M@C materials; 3) The SiO obtained in the above steps x -M@C materials, dispersants, additives, water-soluble carbon sources, and graphene aqueous dispersions are mixed and then granulated to obtain SiO2. x -M@CG precursor, then sintered under a protective atmosphere to obtain SiO x -M@CG composite material; The additives include one or more of polyacrylamide, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, melamine-formaldehyde resin, acetic acid, and lithium acetate.

8. The preparation method according to claim 7, characterized in that, The vacuum pressure at the high vacuum temperature is 0.01~100 Pa; The temperature of the vacuum high temperature is 1300~1500℃; The vacuum high-temperature treatment time is 5~10 hours; The SiO x The D50 particle size of the -M precursor is 100 nm to 10 μm.

9. The preparation method according to claim 7, characterized in that, The dispersant includes one or more of polyethylene glycol, polyacryl alcohol, Tween-60, Tween-80, sodium dodecyl sulfonate, and sodium dodecyl sulfate; The water-soluble carbon source includes one or more of glucose, sucrose, maltodextrin, starch, povidone, and polyacrylic acid; The sintering temperature is 550~800℃; The sintering time is 4 to 6 hours.

10. A lithium-ion battery, characterized in that, Includes positive electrode, negative electrode, membrane, and electrolyte; The negative electrode material includes SiO as described in any one of claims 1 to 4. x -M@CG composite anode material or SiO prepared by the preparation method according to any one of claims 5 to 9 x -M@CG composite anode material; The negative electrode material does not contain a conductive agent.

Citation Information

Patent Citations

  • Silicon-based composite material and preparation method thereof

    CN111653759A

  • Lithium ion battery negative electrode material and preparation method thereof

    CN108054366A

  • PROCESS FOR THE PREPARATION OF SiOx HAVING A NANOSCALE FILAMENT STRUCTURE AND USE THEREOF AS ANODE MATERIAL IN LITHIUM-ION BATTERIES

    US20170260057A1